The influence of coal mining subsidence on the movement and deformation of loess slope in the loess gully area of Northern Shaanxi - Zheng, Beibei; Song, Shijie; Cheng, Xia; Niu, Ruilin; Cheng, Xing; Ruan, Hao; Li, Guodong (Frontiers in Earth Science, 2023)
The results show that: firstly, under any surface slope shape, the average subsidence coefficient (q slope average ) of slope increases with the increase of sand coefficient of coal seam overlying strata, and when the sand coefficient is ≤ 0.71, the q slope average shows a rapid growth trend, with an increase of more than 2.86%; When the "sand coefficient > 0.71", the q slope average tends to be stable, and there is no obvious change. Under any surface slope shape, the q slope average decreases with the increase of sand-mud ratio of coal seam overlying strata on average , that is, the smaller the sand-mud ratio of coal seam overlying strata, the more obvious the influence on slope subsidence. Secondly, when the overburden structure characteristics of any coal seam and the natural slope of the surface slope are ≤ 5°, the q slope average of the convex slope is the largest , ranging from 0.65 to 0.74, and the q slope average with four slope shapes is ranked as follows :convex slope > straight slope ≈ compound slope > concave slope; When the overburden structure characteristics of any coal seam and the natural slope of the surface slope are more than 5°, the q slope average of the concave slope is the largest , ranging from 0.56 to 0.76. The q slope average with four slope shapes is ranked as follows: concave slope > straight slope ≈ compound slope > convex slope. With the increase of natural slope after coal mining subsidence, the q slope average decreases first and then increases with the increase of natural slope, and the inflection point is 15°. Finally, under any surface slope shape, the influence of the structural characteristics of coal seam overburden after coal mining subsidence on the average horizontal displacement of slope (u slope average ) is the same as the subsidence law. Under the characteristics of any coal seam overburden structure, "concave slope with natural slope < 35° and convex slope with natural slope ≥ 35°" have the most obvious influence on the horizontal movement of slope surface.